EFISIENSI DIGITALISASI LAYANAN PADA PRODUK ARRUM HAJI PEGADAIAN - Cheeryl Angelica; Faizi, Faizi (Fakultas Ekonomi Dan Bisnis, Universitas Pembangunan Nasional Veteran Jakarta, 2024)
This research aims to determine the mechanism for financing hajj arrivals through digital pawnshop applications and determine the efficiency of the digitalization implemented. The method and type of research were qualitative and case study. Data collection was carried out using primary sources and data collection techniques of in-depth interviews with informants, observation and documentation. In this research, it was concluded that there are several stages in the Arrum Haji Pegadaian financing mechanism which is carried out through the Pegadaian Digital application. First, register and verify the customer's identity through the Pegadaian Digital application. Then, apply for Arrum Haji financing by fulfilling all the requirements set by Pegadaian. Several factors have been efficient, but there is an obstacle in PT Pegadaian's limited ability to digitalize its services because the process of arrum hajj products involves external parties, so digitalization cannot be involved in its entirety.